LOPED study: looking for an early diagnosis in a late-onset Pompe disease high-risk population. Issue 1 (17th March 2015) - Musumeci, O; la Marca, G; Spada, M; Mondello, S; Danesino, C; Comi, G P; Pegoraro, E; Antonini, G; Marrosu, G; Liguori, R; Morandi, L; Moggio, M; et al.
Abstract : Objective: A multicentre observational study was aimed to assess the prevalence of late-onset Pompe disease (LOPD) in a large high-risk population, using the dried blood spot (DBS) as a main screening tool. Design/methods: 17 Italian neuromuscular centres were involved in the late-onset Pompe early diagnosis (LOPED) study. Inclusion criteria were: (1) age ≥5 years, (2) persistent hyperCKaemia and (3) muscle weakness at upper and/or lower limbs (limb-girdle muscle weakness, LGMW). Acid α-glucosidase (GAA) activity was measured separately on DBS by fluorometric as well as tandem mass spectrometry methods. A DBS retest was performed in patients resulted positive at first assay. For the final diagnosis, GAA deficiency was confirmed by a biochemical assay in skeletal muscle, whereas genotype was assessed by GAA molecular analysis. Results: In a 14-month period, we studied 1051 cases: 30 positive samples (2.9%) were detected by first DBS screening, whereas, after retesting, 21 samples were still positive. Biochemical and molecular genetic studies finally confirmed LOPD diagnosis in 17 cases (1.6%). The median time from the onset of symptoms/signs to diagnosis was 5 years. Among those patients, 35% showed presymptomatic hyperCKaemia and 59% showed hyperCKaemia+LGMW, whereas 6% manifested with LGMW. Conclusions: LOPED study suggests that GAA activity should be accurately screened by DBS in all patients referring for isolated hyperCKaemia and/or LGMW. A timely diagnosis was performed in five patients with presymptomatic hyperCKaemia, but two had already manifested with relevant changes on muscle morphology and MRI. Consequently, enzyme replacement therapy was started in 14/17 patients, including the 2 patients still clinically presymptomatic but with a laboratory evidence of disease progression.